Investigation of the mechanical testing conditions on sensing properties of textile-based strain sensor - (:unkn) unknown (Ege Universitesi, 2017)
The aim of this research study is to investigate the effect of different mechanical test conditions on the sensing properties of proposed knitted strain sensors. In order to fulfill this aim, initially, the effect of quasi-static testing on the sensing properties of sensors is discussed. Thereafter, effect of the tensile testing machine cross head speed on sensor characteristics is investigated. A single design of proposed knitted strain-sensing fabric was devised using computerised flat-bed knitting technology, comprising silver coated nylon conductive yarn with 2 Ω/cm linear resistance and insulating core-spun Lycra yarns with different yarn fineness. It was observed that that sensors produced with the yarn low extension capability showed less imprecision during quasi-static tests and alteration on machine crosshead speed also affected some sensor properties such as hysteresis and linearity but no affect found on gauge factor values. Proposed knitted strain sensing structures can be used for measuring the physiological parameters of the human body, i.e., respiration rate or body articulation.
Keywords: Knitted sensor; Knitting; Silver yarn; Strain sensor; Test conditions